2018
DOI: 10.1002/adfm.201806809
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Engineered Colloids from Edible Materials for Emerging Applications in Designing the Food of the Future

Abstract: Functional and engineered colloids fabricated from edible materials have recently gained a lot of interest for futuristic applications in the field of foods for purposes ranging from microstructure development to delivery of healthpromoting bioactives to manipulation of food-body interactions. This review tackles a very ambitious task of discussing the current understanding of functional colloids within the framework of foods. Physicochemical attributes of several novel complex colloids fabricated from natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 331 publications
(434 reference statements)
0
74
0
3
Order By: Relevance
“…Zein extracted from corn, a protein with the high percentage of nonpolar amino acids (leucine, alanine, and proline) and a sub-product of the food and ethanol industry, is a natural amphiphilic polymer material, which has been extensively studied in biogels, foods, cosmetics and pharmaceutical industry [ 5 , 41 , 42 , 43 ]. As a kind of water-insoluble food-grade alcohol-soluble protein, zein can form colloidal particles through self-assembly without surface-modification when pH deviated from zein isoelectric point [ 44 ].…”
Section: Structure and Composition Of Pickering Emulsionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Zein extracted from corn, a protein with the high percentage of nonpolar amino acids (leucine, alanine, and proline) and a sub-product of the food and ethanol industry, is a natural amphiphilic polymer material, which has been extensively studied in biogels, foods, cosmetics and pharmaceutical industry [ 5 , 41 , 42 , 43 ]. As a kind of water-insoluble food-grade alcohol-soluble protein, zein can form colloidal particles through self-assembly without surface-modification when pH deviated from zein isoelectric point [ 44 ].…”
Section: Structure and Composition Of Pickering Emulsionsmentioning
confidence: 99%
“…Additionally, soy isoflavones, a unique physiologically active substance, has a cholesterol-lowering function. Some studies have reported that glycinin and β-conglycinin, the two major components of soy protein, show peculiar behavior of globular molecules consisting of a hydrophilic shell and a hydrophobic kernel in aqueous environment [ 5 ]. Therefore, soy protein particles have good emulsifying and gelling properties without additional chemical modification [ 48 ].…”
Section: Structure and Composition Of Pickering Emulsionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Valorizing biomass feedstocks and biorefinery downstream products is of utmost importance to improve the viability of a more sustainable economic model . Therefore, in the same way as chemists developing platform molecules from sugar conversion such as hydroxymethylfurfural to synthesize the building blocks of tomorrow, we attempt to extend this concept in developing a sustainable polymer platform that can be easily tunable in terms of architecture and functionality for diverse applications . Among the bioethanol industry side‐stream products like distillers’ grains with solubles and carbon dioxide, corn oil (CnO) figures as one of the major co‐products with an approximated production of 3.6 billion pounds in 2017 in USA .…”
Section: Triple Detection Gpc Results For Pcnomentioning
confidence: 99%